2010
DOI: 10.1007/s11224-010-9716-5
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study on the Ag n H (n = 1–10) clusters

Abstract: Density functional GGA-PW91 method with DNP basis set is applied to optimize the geometries of Ag n H (n = 1-10) clusters. For the lowest energy geometries of Ag n H (n = 1-10) clusters, the hydrogen atom prefers to occupy the two-fold coordination bridge site except the occupation of single-fold coordination site in AgH cluster. After adsorption of hydrogen atom, most Ag n structures are slightly perturbed and only the Ag 6 structure in Ag 6 H cluster is distorted obviously. The Ag-Ag bond is strengthened and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…4, there are two stable structures for Ag 2 H − and Ag 2 H, respectively. The C 2v triangular structure of Ag 2 H predicted in earlier theoretical studies 21,22 turned out to have imaginary frequencies in our calculations. For Ag 2 H − , the lowest energy structure in our results has C ∞ν geometry.…”
Section: B Ag 2 H − and Ag 2 Hsupporting
confidence: 56%
See 1 more Smart Citation
“…4, there are two stable structures for Ag 2 H − and Ag 2 H, respectively. The C 2v triangular structure of Ag 2 H predicted in earlier theoretical studies 21,22 turned out to have imaginary frequencies in our calculations. For Ag 2 H − , the lowest energy structure in our results has C ∞ν geometry.…”
Section: B Ag 2 H − and Ag 2 Hsupporting
confidence: 56%
“…They found that the bridge sites were the most favorable binding positions for hydrogen atom in all cationic, most of the neutral and the larger anionic clusters, while for Ag n H (n = 3) and Ag n H − (n ≤ 4), the top sites of silver clusters were preferred by hydrogen atom. Very recently, Kuang et al 22 investigated the geometries of Ag n H (n = 1-10) using GGA-PW91 DFT method and the results indicated that the hydrogen atom binded stronger on the clusters containing odd number silver atoms, and tended to occupy the two-fold bridge sites. In spite of all those theoretical efforts, structural and electronic characters of silver hydrides were still obscure due to some inconsistent conclusions and the lack of experimental evidences.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved essentially either via wave function based methods for the characterization of small clusters or via density functional theory (DFT) for bulks, surfaces, and middle-size clusters. In particular, the structure of neutral, cationic, and anionic clusters with N up to ∼20–25 has been the subject of numerous DFT investigations for both silver , and gold. Nevertheless, although DFT can handle small to middle-size aggregates, the resulting properties show significant dependence over the functional, and it is only recently that the use of accurate functionals such as revTPSS, M06, , SOGGA, or RPA methods seems to have lifted the uncertainties about the structural and electronic features of even small-size clusters. For instance, the 2D–3D transition in gold clusters has been in debate for some time and only recent theoretical studies provided results in agreement with the experimental data .…”
Section: Introductionmentioning
confidence: 99%
“…All calculations were performed using the suite program of Gaussian 09 . The pw91pw91 hybrid exchange–correlation functional , was used, which has shown good reliability and accuracy in previous reports. For silver, the effective core potential (ECP) of Lanl2 combined with the DZ basis set was adopted, while for O and C atoms, the full electron basis set of 6-31G­(d) was employed. All stationary points on the potential energy surface (PES) were verified by calculated vibrational frequencies at the same theoretical level as used in the geometry optimization. To locate a transition state (TS), a relaxed PES scan was carried out first to find the structure with the highest energy on the reaction path.…”
Section: Computational Details and Modelsmentioning
confidence: 99%